2019
DOI: 10.1002/jrs.5619
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Raman spectroscopy in diabetes detection based on biomarker Raman bands and in antidiabetic efficacy studies of herbal extract Rotheca myricoides Hochst

Abstract: Diabetes is a disease characterized by hyperglycaemia because of insufficient or nonproduction of insulin from the pancreas. Establishing prediabetic and diabetic condition often involves monitoring levels of glucose and some amino acids in blood using nonrapid and label‐dependent methods. This work reports on a method with a potential of being used for quick label‐free detection of diabetes mellitus type II based on Raman spectroscopy of blood applied onto a conductive silver‐smeared glass slide. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Here, the herbal extract Rotheca myricoides Hochst and the antidiabetic drug pioglitazone were shown to result in the decrease in intensity of the spectroscopic bands associated with the aforementioned biomolecules; PCA also indicated spectral differences existed between the various groups. 48 Both papers indicate an interesting potential for the early identification and treatment monitoring of T2DM based on novel and alternative Raman spectroscopic biomarkers. Early detection of the disease can help mitigate potential issues which arise as a result of it, as well as provide the afflicted individual with more effective treatment opportunities.…”
Section: Monitoring Novel Biomarkers For Indicating Diabetesmentioning
confidence: 99%
“…Here, the herbal extract Rotheca myricoides Hochst and the antidiabetic drug pioglitazone were shown to result in the decrease in intensity of the spectroscopic bands associated with the aforementioned biomolecules; PCA also indicated spectral differences existed between the various groups. 48 Both papers indicate an interesting potential for the early identification and treatment monitoring of T2DM based on novel and alternative Raman spectroscopic biomarkers. Early detection of the disease can help mitigate potential issues which arise as a result of it, as well as provide the afflicted individual with more effective treatment opportunities.…”
Section: Monitoring Novel Biomarkers For Indicating Diabetesmentioning
confidence: 99%
“…Thus, it has been shown that Raman spectroscopy can be a reliable method for diabetes screening in blood samples. It can also potentially be used to evaluate the effectiveness in diabetes therapy [181,183].…”
Section: Raman Spectroscopymentioning
confidence: 99%
“…They showed it is possible to highlight certain structures of lignin with Raman spectroscopy, because low amounts of a compound do not necessarily mean weak features in the spectrum. Chege et al [ 66 ] demonstrated the utility of Raman spectroscopy in diabetes detection based on biomarker Raman bands and in antidiabetic efficacy studies of the herbal extract Rotheca myricoides Hochst. They described a method with a potential of being used for quick label‐free detection of diabetes mellitus type II based on Raman spectroscopy of blood applied onto a conductive silver‐smeared glass slide.…”
Section: Biosciencesmentioning
confidence: 99%